Skolen der ikke stopper med ikke at etablere sig - Bjerre, Henrik Jøker (Slagmark - Tidsskrift for idéhistorie, 2018)
The history of the Slovenian School is more diverse, and longer, than one might expect. To trace the origins of what is today often referred to as the Slovenian School, one has to go back to 1971, when Rastko Močnik and Slavoj Žižek started taking up contemporary French structuralism to find new approaches to understanding the events in Europe and elsewhere, from Che Guevara to the Prague Spring. This article tracks down the major historical points in the development of the school, as well as some of its major philosophical assumptions, and argues that it has never really established itself as one. And that this continues to be one of its major virtues.